MONOTOWNS AND SUSTAINABLE DEVELOPMENT: THE CONTRIBUTION OF GRASSROOTS TO THE FORMATION OF URBAN NARRATIVES - Didenko, Kateryna (Theory and practice of design, 2025)
This study focuses on analyzing the role of grassroots initiatives in Visaginas, Lithuania, a post-industrial monotown undergoing structural transformation following the closure of the Ignalina Nuclear Power Plant. Purpose. The primary aim is to examine how bottom-up initiatives can advance post-Soviet urban development in the context of demographic decline, social vulnerability, and limited resources, as well as how these initiatives contribute to the formation of new urban sustainability narratives. Methodology. The research is grounded in an interdisciplinary approach that integrates urban analysis, qualitative sociological methods – including semi-structured interviews and participant observation – and a spatial-cultural analysis of local practices. This combination allows for a comprehensive understanding of both the material and symbolic dimensions of urban transformation and the interactions between residents, activists, and professional stakeholders. Results. The findings indicate that grassroots initiatives play a pivotal role in enhancing social cohesion and activating urban life. They foster cultural interaction, increase attention to environmental concerns, and reimagine the city as a space of sustainable development. The study demonstrates that the synergy between local residents and professionals creates a foundation for the emergence of inclusive and resilient practices. At the same time, it identifies barriers that challenge the long-term sustainability and scalability of these initiatives, ranging from resource scarcity to limited institutional support. Scientific novelty. The originality of this research lies in the integration of urban analytical frameworks with an assessment of the transformative potential of local actions within a multicultural post-industrial setting. The study highlights mechanisms of «sustainability from below» and illustrates how grassroots initiatives can reshape dominant urban narratives under conditions of structural crisis. Practical relevance of the study lies in identifying practices that promote and factors that hinder the sustainability and development of grassroots initiatives. The mechanisms identified may be useful to other single-industry towns in their transition to a more sustainable future.